An empirical study of reliable networking for vehicular networks using IEEE 802.11n. (1st January 2014) - Lee, Seungbae; Lim, Alvin; Yang, Qing
The IEEE 802.11n technology is becoming more and more prevalent in wireless networks due to its significant enhancements in network performance. To examine whether the reliability of 802.11n is sufficient for vehicular networks, we conducted extensive experiments on inter-vehicle and intra-vehicle communications in vehicular environments. From this empirical study, we found that 802.11n provides high performance with stable throughput and reliable coverage in most cases. However, 802.11n protocols do not detect frequent changes of propagation and polarisation due to vehicle mobility and its rate adaptation algorithms improperly select multi-stream rates under channel fading conditions, although single-stream rates perform better. Moreover, an optimal antenna alignment that enables High Throughput (HT) operation using parallel data streams needs further investigation in vehicular environments. Our findings have profound implications on the protocol design and appropriate configuration for reliable networking in vehicular networks using 802.11n.